Muscle Biological Characteristics of Differentially Expressed Genes in Wujin and Landrace Pigs - Hong XU; Ying HUANG; Wei-zhen LI; Ming-hua YANG; Chang-rong GE; Xi ZHANG; Liu-an LI; Shi-zheng GAO; Su-mei ZHAO (Journal of Integrative Agriculture, 2014)
The biological chemistry would be responsible for the meat quality. This study tried to investigate the transcript expression profile and explain the characteristics of differentially expressed genes between the Wujin and Landrace pigs. The results showed that 526 differentially expressed genes were found by comparing the transcript expression profile of muscle tissue between Wujin and Landrace pigs. Among them, 335 genes showed up-regulations and 191 genes showed down-regulations in Wujin pigs compared with the Landrace pigs. Gene ontology (GO) analysis indicated that the differentially expressed genes were clustered into three groups involving in protein synthesis, energy metabolism and immune response. Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis found that these differentially expressed genes participated in protein synthesis metabolism, energy metabolism and immune response pathway. The Database for Annotation, Visualization and Integrated Discovery (DAVID) analysis of protein function and protein domains function also confirmed that differentially expressed genes belonged to protein synthesis, energy metabolism and immune response. Genes related protein synthesis metabolism pathway in Landrace was higher than in Wujin pigs. However, differentially expressed genes related energy metabolism and immune response was up-regulated in Wujin pigs compared with Landrace pigs. Quantitative real-time RT-PCR on selected genes was used to confirm the results from the microarray. These suggested that the genes related to protein synthesis, energy metabolism and immune response would contribute to the growth performance, meat quality as well as anti-disease capacity.